The Origin of Back-Arc Spreading in The Eastern Edge of Scotia Plate - Indra Budi Prasetyawan (Buletin Oseanografi Marina, 2016)
The origin and evolution of  back-arc spreading in the eastern edge of Scotia Plate will be discussed in this paper. The Scotia Plate is a tectonicplate on the edge of the South Atlantic and Southern Ocean, located between the South American and Antartic plates. The East Scotia Ridge (ESR) in the eastern edge of Scotia Plate, forned due to subduction of the South American plate beneath the South Sandwich plate along the South Sandwich Island arc. The methods and techniques of data acquisition used were data from absolution motions and data from magnetic anomalies and bathymetric data. Magnetic anomalies and  bathymetric data that used in this paper consist of two sets data. First, magnetic anomalies and  bathymetric data which were obtained by aboard HMS Endurance in the 1969-70 austral summer, and the second, magnetic anomalies and  bathymetric data which were obtained after removal of the International Geomagnetic Reference Field (IGRF). Absolution motion analyses in the subduction zones of Sandwich plate results that form back-arc spreading in East Scotia Ridge showing high deformation for slow moving upper plates. Where back-arc spreading is associated with upper plate retreat that reaches 26.9 mm/year and have back-arc deformation style consistent with upper plate absolute. Key Words: Geological oceanography, Scotia plate, back-arc spreading